TCRβ spectratyping in RA: evidence of clonal expansions in peripheral blood lymphocytes. Issue 5 (1st May 1998) - Hall, F C; Thomson, K; Procter, J; McMichael, A J; Wordsworth, B P
Abstract : OBJECTIVE: To compare the TCRβ repertoire of peripheral blood CD8 enriched (CD8+) and depleted (CD8−) T cells in rheumatoid arthritis (RA) patients and controls using CDR3 length analysis (spectratyping). METHODS: CD8+ and CD8− T cells were separated from 14 RA patients and 12 controls, using magnetic beads coated with anti-CD8 monoclonal antibodies. cDNA was prepared as the template for amplification with 22 Vβ-Cβ primer pairs. The products were resolved by electrophoresis in an ABI373 sequencer using GENESCAN software. Expansions were identified as dominant CDR3 lengths, where the area underlying the corresponding peak exceeded the sum of the areas of the two adjacent peaks. This method was validated by sequencing 10 samples displaying dominant peaks. The expansion frequencies in RA patients and controls were compared using the χ 2 test statistic. RESULTS: Dominant peaks were evident in several Vβ families. They were more frequent in RA patients in both the CD8+ subset (RA normalised frequency 10.6; control normalised frequency 8.0; p=0.03) and the CD8− subset (RA normalised frequency 2.9; control normalised frequency 1.5; p=0.02). Sequencing of 10 samples exhibiting dominant peaks revealed an unequivocal clonal expansion in nine (90%). CONCLUSIONS: RA patients exhibited a significantly increased frequency of T cell expansions both in the CD8+ and CD8− subsets. This phenomenon may reflect the proliferation of autoreactive cells, a non-specific expansion of memory T cells in response to pro-inflammatory cytokines or a defect of T cell regulation that predates the onset of RA and may itself predipose to disease.